2001
DOI: 10.3758/bf03200506
|View full text |Cite
|
Sign up to set email alerts
|

The Ponzo illusion and the perception of orientation

Abstract: A new theory, called the tilt constancy theory, claims that the Ponzo illusion is caused by the misperception of orientation induced by local visual cues. The theory relates the Ponzo illusion-along with the Zöllner, Poggendorff, Wündt-Hering, and cafe wall illusions-to the mechanisms that enable us to perceive stable orientations despite changes in retinal orientation or body orientation. In Experiment 1, the magnitude of the misperception of orientation was compared with the magnitude of the Ponzo illusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 57 publications
3
48
0
1
Order By: Relevance
“…This is particularly the case for the Ponzo illusion task, which, despite being a well-studied effect of visual perception, as reviewed and discussed by Prinzmetal and colleagues,30 does not have the history of use with fMRI that the reversing checkerboard task has. If the child with Alice in Wonderland syndrome had shown a global change in BOLD signal relative to the control participant, it might be argued that the results simply reflect individual differences in BOLD signal responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly the case for the Ponzo illusion task, which, despite being a well-studied effect of visual perception, as reviewed and discussed by Prinzmetal and colleagues,30 does not have the history of use with fMRI that the reversing checkerboard task has. If the child with Alice in Wonderland syndrome had shown a global change in BOLD signal relative to the control participant, it might be argued that the results simply reflect individual differences in BOLD signal responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Results from cross-cultural studies have provided support to experience-based explanations [7]. Although alternative accounts have been suggested [8], there has thus far been no direct test of the necessity of visual experience for engendering susceptibility to these illusions.…”
mentioning
confidence: 99%
“…Predebon (1992Predebon ( , 1994, after extensive investigations of his own, concluded that assimilation theories provide the most satisfactory explanations of reversed Müller-Lyer illusions. Prinzmetal, et al (2001) list additional criticisms of assimilation theory but, because their critique refl ects an acute misunderstanding of the theory, a brief description of assimilation theory is necessary. Fig.…”
Section: The Crucial Experimentsmentioning
confidence: 99%